SÓYLEWI TOLÍQ RAWAJLANBAǴAN BALALARDÍŃ BAYLANÍSLÍ SÓYLEWIN QARAQALPAQ XALÍQ ERTEKLERI ARQALÍ RAWAJLANDÍRÍW - Shakirova, S.Y. (SCIENCE and SOCIETY, 2025)
This article discusses the importance of Karakalpak folk tales in the development of coherent speech in children with general speech underdevelopment and the speech characteristics of children with connected speech underdevelopment.